ANALISIS TINGKAT KEPUASAN ATAS KUALITAS PELAYANAN JASA PADA HOTEL RATU MAYANG GARDEN PEKANBARU - Saputra, Alfin; -, Jushermi; Rahayu, Deny Danar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to determine the level of satisfaction with the quality of service at the Ratu Mayang Garden Hotel in Pekanbaru and determine strategies satisfaction over the quality of service at the Ratu Mayang Garden Hotel in Pekanbaru.The population in this study were all guests who use the services of hotel rooms at Ratu Mayang Garden Hotel Pekanbaru recorded from the beginning of 2012 until the end of 2012 as many as 31.557 people. methods of sampling in this study using accidental sampling method and the number of samples is 100 people. To analyze the data in this study will use Importance Performance Analysis (IPA) technique. The results of this study stated that the average score of hope that assessed based on five (5) indicators i.e. tangible, reliability, responsiveness, assurance and empathy is at 3.62 means that the level of consumer expectations for service have a satisfied category. The average score balanced performance assessed by 5 (five) indicators i.e. tangible, reliability, responsiveness, assurance and empathy is equal to 3.49 means that the level of consumer expectations for service have a Neutral category. However, this score is lower than the scores of level consumer expectations. Based on calculations, the degree of correspondence between expectations and performance in the service of the Ratu Mayang Garden Hotel lies in the range of 81% - 100% were categorized Great Fit. The results of the analysis matrix Cartesian diagram shows that tangible, reliability and responsiveness is a variable that is a priority of consumer/hotel guests and based on performance assessment thre are three variables that need to be maintained i.e. assurance and empathy in terms of the level of expectation in the category less than expected while in terms of the level of performance is considered excessive that needs to be reduced, especially in terms of the relationship between the employees and hotel guests.Keywords: Tangible, Reliability, Responsiveness, Assurance, Empathy